L-Proline-Catalysed the Synthesis of Aromatic Aldehydes and Ketones and their Acridione Derivatives at Room Temperature. (August 2015) - Wang, Fang-Ming; Bao, Dan; Hu, Bing-Xiang; Zhou, Ze-Yu; Huang, Deng-Deng; Chen, Li-Zhuang; Liu, Yang-Mei
A series of xanthene derivatives were prepared from cyclohexane-1, 3-dione and aromatic aldehydes through Knoevenagel–Michael and cyclisation reactions in methanol:ethanol mixture (1:1), catalysed by a very small amount ofl -proline at room temperature. Isomeric tetraketones were synthesised from dimedone and aromatic aldehydes under the same condition. Condensation of them with amines gave acridione derivatives. The crystal structure of an acridione was obtained and determined by X-ray single-crystal diffraction.